2022
DOI: 10.1101/2022.06.06.494961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-silico identification of potential antigenic proteins in Bartonella bacilliformis for the serological diagnosis of Carrions’ disease

Abstract: The current methods for inferring antigenic, pathogenic or virulence factors in bacteria include in-silico or computational tools. Bartonella bacilliformis, the causal agent of Carrion's disease (CD) is a Gram-negative microorganism transmitted by the sand fly Lutzomya verrucarum mainly in Peruvian Inter-Andean valleys. A better understanding of the pathogenicity of B. bacilliformis, the implementation of serological diagnostic methods and the development of candidate vaccines for the control of CD could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
1
1
0
Order By: Relevance
“…This statement is supported by Paul et al who described potential sub-speciation in isolates related to Ver097, such as, for instance, LA6.3, and Luc-Uba, all three of which were isolated from Ancash [34]. As mentioned, our findings show amino acid mutations that could affects protein functions, so we consider these non-synonymous mutations must be carefully analyzed to avoid inaccuracy during an in-silico analysis [35].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 83%
“…This statement is supported by Paul et al who described potential sub-speciation in isolates related to Ver097, such as, for instance, LA6.3, and Luc-Uba, all three of which were isolated from Ancash [34]. As mentioned, our findings show amino acid mutations that could affects protein functions, so we consider these non-synonymous mutations must be carefully analyzed to avoid inaccuracy during an in-silico analysis [35].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 83%
“…The analysis revealed that one prophage of Klebsiella pneumoniae harbored Peptidoglycan DD-metalloendopeptidase family protein and undecaprenyl-phosphate glucose phosphotransferase, which are known virulence factors [42]. Additionally, the prophage of Pseudomonas aeruginosa was found to contain Phenazine biosynthesis protein PhzF, which is an isomerase involved in phenazine biosynthesis and has been linked to virulence in P. aeruginosa [43]. Therefore, those prophages which are detected to producing virulent genes are rejected.…”
Section: Discussionmentioning
confidence: 99%